TINGKAT KEBERHASILAN PELATIHAN MEMBATIK ECO GREEN DENGAN MENGGALI POTENSI ALAM DI KAMPUNG ADAT CIREUNDEU-CIMAHI - Ariesa Pandanwangi; Ida Ida; Belinda Sukapura Dewi; Dewi Isma Aryani; Rosida Tiurma Manurung (Jurnal Abdimas Bina Bangsa, 2023)
The people of the Cireundeu-Cimahi traditional village are Sundanese indigenous people who have preserved traditions from generation to generation. Cireundeu is famous for its natural potential in the form of Sampeu which has not been fully exploited. The problem is, the government is trying to improve the skills of citizens. One of them is providing batik training by utilizing natural potential to become batik motifs. The goal is to improve skills so that economic conditions can also develop. The method used is the SL (Service Learning) method which involves students. Participants totaled 20 people. The results of this training participants can make batik motifs that were initiated from natural potential. The objects are dominated by shapes made of cassava leaves, which is interesting that almost all of his works are marked with his name written in Sundanese script. The visualized composition varies from asymmetrical and centered. The colors combined are also very interesting, such as a combination of color gradations from red to yellow, dark blue to light blue gradations